Correction: Topical HPMC/S-Nitrosoglutathione Solution Decreases Inflammation and Bone Resorption in Experimental Periodontal Disease in Rats. - Conceição S Martins; Renata F C Leitão; Deiziane V S Costa; Iracema M Melo; Glaylton S Santos; Vilma Lima; Victor Baldim; Deysi V T Wong; Luana E Bonfim; Cíntia B Melo; Marcelo G de Oliveira; Gerly A C Brito (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0153716.].